Research on the influence of body image on college students’ weight-loss intention: chained intermediary analysis of self-efficacy and self-esteem - Yiyi, Ouyang; Xue, Xiong; Jiong, Luo; Yanhui, Zhang (Frontiers in Psychology, 2024)
Purpose This paper aims to explore the relationship between body image, self-efficacy, self-esteem, and weight-loss intention among college students, offering insights to promote healthy and confident lifestyle habits. Methods Undergraduate students from western China were selected using a stratified random sampling method. Data were analyzed using SPSS 19.0 and AMOS 21.0 statistical software. Results (1) Body image showed a significantly positive correlation with self-efficacy and self-esteem but a negative correlation with weight-loss intention. Self-efficacy exhibited a significantly positive correlation with self-esteem and a negative correlation with weight-loss intention, while self-esteem was significantly negatively correlated with weight-loss intention. (2) Body image directly impacted weight-loss intention [Effect Size (ES) = −0.120]. Self-efficacy (ES = −0.069) and self-esteem (ES = −0.119) played significant mediating roles between body image and weight-loss intention, respectively. (3) The chained intermediary role of self-efficacy and self-esteem also reached significance (ES = −0.038). Conclusion Body image conducts effect on the degree of weight-loss intention among college students through direct ways or indirect ways such as the intermediary role of self-efficacy and self-esteem, and also the chained intermediary role of self-efficacy and self-esteem. In addition, self-esteem is another key factors affecting college students’ weight-loss intention.